Income taxation made easy - Ballada, Win.; Ballada, Susan (Manila, Philippines : DomDane Publisher, 2014)
They have exerted efforts to distill information into more meaningful and understandable discussions.
1. Basic principles -- 2.Taxation of individuals -- 3. Taxation of corporations -- 4. Minimum corporate income tax -- 5. Taxation of estates and trusts -- 6. Taxation of partnership and partners -- 7. Gross income -- 8. Fringe benefits -- 9. Gains and losses from dealings in property -- 10. Allowable deductions -- 11. Withholding taxes -- 12. Foreign tax credit -- 13. Penalties -- 14. Returns and payment of tax -- 15. Accounting methods and periods -- 16. Remedies -- 17. Compliance requirements
Keywords: INCOME TAXATION -- LAW -- PHILIPPINES